Pentafluorobenzyl esterification of haloacetic acids in tap water for simple and sensitive analysis by gas chromatography/mass spectrometry with negative chemical ionization. (January 2015) - Zhao, Can; Fujii, Yukiko; Yan, Junxia; Harada, Kouji H.; Koizumi, Akio
Highlights: Haloacetic acids (HAAs) levels in tap water are determined. Pentafluorobenzyl esterification is used for pretreatment. Gas chromatography/mass spectrometry with negative chemical ionization is used. Method has low detection limits (8–94 ng L −1 ) and good recovery rates (89–99%). The HAAs concentrations are in range 0.54–7.83ƒ Kg L −1 in Japanese tap water. Abstract: Chlorine is the most widely used disinfectant for control of waterborne diseases in drinking water treatment. It can react with natural organic matter in water and form haloacetic acids (HAAs). For analysis of HAA levels, derivatization with diazomethane is commonly recommended as the standard methodology in Japan. However, diazomethane is a carcinogenic alkylating agent. Therefore, in this study, a safe, simple, and sensitive quantification method was developed to monitor HAAs in drinking water. Pentafluorobenzyl esterification was used for pretreatment. The pentafluorobenzyl-ester derivative was detected by gas chromatography–negative ion chemical ionization-mass spectrometry analysis with very high sensitivity for HAAs analysis. The method has low detection limits (8–94 ng L −1 ) and good recovery rates (89–99%) for HAAs. The method was applied to 30 tap water samples from 15 cities in the Kansai region of Japan. The levels of HAAs detected were in the range 0.54–7.83 μg L −1 . Dichloroacetic acid, trichloroacetic acid, and bromochloroacetic acid were the major HAAs detected in most of the tap water, and accounted for 29%, 20% and 19% of the total HAAs, respectively. This method could be used for routine monitoring of HAAs in drinking water without exposure of workers to occupational hazards.